ANALYSIS OF INFORMATION SYSTEMS EMPLOYEES WITHDRAWAL IN PT. XYZ - Kurniawan Kurniawan; Dra. Ida Ayu Wiastiti, MKom (Jurnal Sistem Informasi, 1997)
Computerization is an alternative in dealing with solving the problems faced in thecurrent system. Related to that, storage data will be better and safer and easier torepair. Presentation information will be faster. Application of this information systemat PT. XYZ will facilitate the withdrawal of employees so that data processingbecomes faster and easier.